A Reproducible Bioprinted 3D Tumor Model Serves as a Preselection Tool for CAR T Cell Therapy Optimization - Grunewald, Laura; Lam, Tobias; Andersch, Lena; Klaus, Anika; Schwiebert, Silke; Winkler, Annika; Gauert, Anton; Heeren-Hagemann, Anja I.; Astrahantseff, Kathy; Klironomos, Filippos; Thomas, Alexander; Deubzer, Hedwig E.; et al. (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T cell performance against solid tumors in mouse models and clinical trials is often less effective than predicted by CAR construct selection in two-dimensional (2D) cocultures. Three-dimensional (3D) solid tumor architecture is likely to be crucial for CAR T cell efficacy. We used a three-dimensional (3D) bioprinting approach for large-scale generation of highly reproducible 3D human tumor models for the test case, neuroblastoma, and compared these to 2D cocultures for evaluation of CAR T cells targeting the L1 cell adhesion molecule, L1CAM. CAR T cells infiltrated the model, and both CAR T and tumor cells were viable for long-term experiments and could be isolated as single-cell suspensions for whole-cell assays quantifying CAR T cell activation, effector function and tumor cell cytotoxicity. L1CAM-specific CAR T cell activation by neuroblastoma cells was stronger in the 3D model than in 2D cocultures, but neuroblastoma cell lysis was lower. The bioprinted 3D neuroblastoma model is highly reproducible and allows detection and quantification of CAR T cell tumor infiltration, representing a superior in vitro analysis tool for preclinical CAR T cell characterization likely to better select CAR T cells for in vivo performance than 2D cocultures.